Georgia's security environment and combating terrorism - new challenges and threat in 21st century - Maisaia, Vakhtang (Array, 2020)
The article discusses Georgia’s security environment in the lens of terrorism. Taking into account that 21st century took the importance of terrorism on a global scale it became not only concern of word politic but domestic politics as well. It is the act of violence initiated by humans and are often of a malicious nature. That is a reason for increased attention toward it. Although Georgia is not among the countries with high risk of terrorist attack, there are some challenges in this respect. However, before estimating the threats coming from terrorism, first, we need to clarify conceptual meaning of security for Georgia and what are the main threats for it. Security environment in Georgia is linked with Russian occupation and terrorism, especially with Chechen fighters in Syria and Iraq who sometimes are associated with Pankisi gorge (east Georgia). Returning back these fighters in Georgia may cause some danger for its security. But Georgia has close ties with international society and it cooperates with different organizations with this respect.